A Tale of Misplaced Intercostal Chest Drain Tube (Bangladesh Critical Care Journal, 2025)
Intercostal chest drain tube placement is one of the many invasive bedside procedures done at ICU. Misplacement of the tube is one of the common complications. Misplacement into liver is rare but life threatening. Here we present a case of a patient with right sided hemothorax having a misplaced chest drain tube.Bangladesh Crit Care J September 2025; 13 (2): 128-130